Biodiversity in Saco da Fazenda, Itajaí-SC estuary - Olinto Branco, Joaquim; Freitas Júnior, Felipe; Alves Fracasso, Hélio Augusto; Barbieri, Edison (O Mundo da Saúde, 2011)
Estuaries are characterized by presenting a high biological productivity working as important feeding, breeding, nursery and recruitment areas for a large diversity of organisms. However, the increasing of human occupation associated to an intensive economic exploration, has led to a gradual increase of habitat degradation of such areas. Saco da Fazenda (Itajaí, Santa Catarina state, Brazil) suffers intense anthropic impact, receiving domestic sewage discharge, solid residues and dredging activities. The aim of this work was to analyze the quail-quantitative composition of the crustaceans, fishes and birds, and the probable impacts of dredging activities of its species. The ichthyofauna assemblage was composed by 51 species, 42 genera and 23 families, with the white mullet, Mugil curema being the most abundant species in 2001-2002 and 2003-2005, while the atlantic sabretooth Anchovy Lycengraulis grossidens and the Caitipa mojarra Diapteurs rhombeus dominated in 2000-2001 and 2002-2003 respectively. True crabs and shrimps are distributed among five families and ten species, where Callinectes danae was the most abundant. Crabs were represented by five species and two families, being Uca uruguayensis the most abundant species. The avifauna was characterized by 50 species where seven were classified as shorebirds, 39 were limnic waterbirds and four species were border inhabitants or visitors coming from the Atlantic Forest. The families Ardeidae, Scolopacidae, Laridae and Charadriidae contributed with 64,0% of the species, being Phalacrocorax brasilianus (Gmelin, 1789) and Larus dominicanus Lichtenstein, 1823 the predominant ones. Despite the benthonic habitat degradation and the mortality of Ariidae, Paralichthydae and Portunidae specimens during the period of dredging activities, it was observed an increment in species abundance and richness after the accomplishment of these activities, probably associated with depth increase, which improved local water circulation patterns, therefore favoring the entrance of fishes and crustaceans in the ecosystem.